Ternary sulfides BaLa2S4 and CaLa2S4 as promising photocatalytic water splitting and thermoelectric materials: First-principles DFT calculations. (3rd September 2020) - Batouche, M.; Seddik, T.; Vu, Tuan V.; Vo, Dat D.; Tong, Hien D.; Hoat, D.M.; Khyzhun, O.Y.
Abstract: Both ternary sulfides, BaLa2 S4 and CaLa2 S4, are found to possess a suitable band gap for absorbing visual light; moreover, the E C B and E V B are at right positions allowing the photo-generated electron/hole pairs to split water. The valence band of BaLa2 S4 (CaLa2 S4 ) are characterized by high peaks at −1 eV and −2 eV, and strong hybridization of S/La- p and Ba- s (Ca- s / p ) states. These features help to enhance the separation of electron/hole pairs. Meanwhile, the conduction band has high peak at 3 eV, which is mostly constructed by hybridization of La- f, La- d and Ba- s (Ca- s / p ) states. The conduction band's smooth dispersion is favorable for inter-band transition, thus it enhances the absorption rate of two considered compounds. The Ba/Ca/La–S bonds are predominantly covalent with electronegativity difference of about 31–38%. The large difference in effective mass between electron and hole enhances the separation of electron/hole pairs. CaLa2 S4 and BaLa2 S4 are p-type semiconductors with positive thermopower S of about 229.8 μ V / K and 234.8 μ V / K, respectively, at Fermi level (μ = 0) and temperature 300 K. Both materials show good thermoelectric performance for hole concentration being in the range 1 × 10 19 –1x10 21 cm -3 . The electronic figure of merit Z T e marks the highest value of about 0.95 and 0.97 at 2 × 10 19 cm -3 for CaLa2 S4 and BaLa2 S4, respectively. Graphical abstract: Image 1 Highlights: Band structure of Ba/CaLa2 S4 is suitable for light absorption and water splitting. Electronic structure is favorable for electron/hole separation and charge mobility. BaLa2 S4 and CaLa2 S4 are p-type semiconductors. Figure of merit is 0.95 (CaLa2 S4 ) and 0.97 (BaLa2 S4 ) at 2x10 19 cm -3 .